Peran Perseroan sebagai Pelaku Usaha Perdagangan Karbon untuk Mitigasi Perubahan Iklim - Andrian, Mazhar; Harahap, Rani Nuraeni; Purnomo, Michael (Jurnal Locus Penelitian dan Pengabdian, 2025)
Climate change caused by greenhouse gas emissions has become a global issue, resulting in various regulations related to climate change mitigation. Indonesia, as a country with high emissions levels, is committed to reducing emissions through carbon trading mechanisms. Carbon trading is a market-based scheme that allows companies to buy or sell emission permits as part of a climate change mitigation strategy. This study aims to analyze the role of companies as business actors in the carbon trading mechanism in Indonesia and the effectiveness of the regulations governing it. The approach used in this study is normative juridical, analyzing various regulations such as Presidential Regulation Number 98 of 2021 concerning the Implementation of Carbon Economic Value and Financial Services Authority Regulation Number 14 of 2023 concerning Carbon Trading Through Carbon Exchanges, as well as various international regulations related to carbon trading. The results show that carbon trading is not only an instrument for reducing carbon emissions but also has a positive impact on the economy by attracting green investment and encouraging low-carbon technological innovation. Companies play a crucial role in this system, both as carbon trading actors and as subjects obliged to contribute to emission reduction. However, challenges remain in implementation, such as regulatory compliance, transaction transparency, and the effectiveness of carbon trading mechanisms. Therefore, strengthening policies and strict oversight are needed so that carbon trading can become an effective instrument in achieving the Net Zero Emission (NZE) target by 2060 and encouraging sustainable development.